Brazil’s Regulatory Context for Using New Approach Methodologies (NAMs) on the Registration of Products - Villela, Izabel Vianna; Machado, Miriana da Silva (Frontiers in Toxicology, 2022)
New Approach Methodologies (NAMs) are any non-animal-based approaches that can provide information in the context of chemical hazard and safety assessment. The goal is to develop information with equivalent or better scientific quality and relevance than provided by traditional animal models. Started by ethical issues, these approaches are gaining regulatory relevance in different global agencies. Since 2008, with the enactment of the Arouca Law - the first Brazilian legislation dedicated to laboratory animals, NAMs are gathering pace in Brazil's regulations. Specific regulations from different sectors include the acceptance of these new methods. However, some regulation is controversial about what is needed to address specific toxicological endpoints. The resulting regulatory uncertainty induces companies to keep on adopting the traditional methods slowing NAM's development in the country. This work brings a perspective of the regulatory acceptance of NAMs in Brazilian Legislations for the registration of pharmaceuticals, medical devices, food/supplements, and agrochemical products. This text discusses the main issues of NAMs adoption for each specific regulation. Therefore, legal acceptance of NAMs results in Brazil is still a process in progress. A collective effort including regulators, industry, Contract Research Organizations (CROs), and the academic environment is needed to build regulatory confidence in the use of NAMs.